Studi Fenomenologis tentang Fatherless pada Narapidana Perempuan - Pramudito, Anselmus Agung; Arini, Diana Putri; Utomo, Irene Prilia Bevi (Universitas Andalas, 2024)
Fatherlessness is a phenomenon that can have various negative impacts on children's development into adulthood. The absence of a father's role, especially for women, means that individuals do not have appropriate role models in enforcing discipline and implementing principles. This can become problematic behavior and has the potential to lead to crime. This research aims to explore the image of fatherlessness among female prisoners. This research uses a qualitative research method with a phenomenological approach involving several women who are prisoners at the class IIA Palembang Penitentiary. Semi-structured in-depth interview methods, unstructured observation, and member checking. Data obtained from the field will be analyzed using interpretative phenomenological analysis (IPA) techniques. The results of this research found main themes: lack of affection, longing for a father figure and hope for family unity.